Studying the Bible The Tanakh and Early Christian Writings - Eiselein, Gregory; Goins, Anna; Wood, Naomi J. (Open textbook library., 2019)
Studying the Bible: The Tanakh and Early Christian Writings is a university-level, textbook introduction to the study of the Bible, its literary forms, and historical and cultural contexts. This textbook is a companion to the Bible courses taught in the English Department at Kansas State University, in particular ENGL 470 The Bible, though it is available for use in other courses and contexts. This textbook examines the Hebrew Bible (also known as the Tanakh) and the early Christian writings of the New Testament. It is an introduction to the analysis of biblical texts, their histories, and their interpretations. The emphasis throughout this textbook is on the literary qualities of these biblical texts as well as their cultural and historical contexts.